No instructions were included, but I will assume that you are supposed to solve this linear equation.
To solve linear equations, undo whatever has been done to the variable. For instance:
. . . . .x + 5 = 3
. . . . .x + 5 - 5 = 3 - 5
. . . . .x = -2
. . . . .3x = 5
. . . . .(3x)/3 = (5)/3
. . . . .x = 5/3
. . . . .5 - 2x = 3
. . . . .5 - 5 - 2x = 3 - 5
. . . . .-2x = -2
. . . . .(-2x)/(-2) = (-2)/(-2)
. . . . .x = 1
...and so forth. Apply that process to your exercise.
If you get stuck, please reply showing what you have tried. Thank you.
Eliz.